Partnership Modelling of Entrepreneurial, Digital and Performance Competencies among Coffee SME’s in Bener Meriah Regency - Muhammad Reza Aulia; Rizki Agam Syahputra (Universitas Teuku Umar, 2023)
The current initiative on SMEs development suggest that effective partnership programs play a pivotal role in enhancing SME competitiveness. However, current research in the area of partnership programs, specifically their impact on SMEs performance, remains limited. Therefore, partnerships need to be examined with an emphasis on moderator variables to assess their impact on various aspects. This research presents an objective to determine a partnership program impact on SME performance. To fully understand the dynamic of the study, this research propose a Partnership Program model consists of three exogenous variables: Entrepreneurial Competence (KK), Partnership Program (PK), and Digital Competence (KD), and one endogenous variable: SME Business Performance. To analyse the data in the research, this research employs the Partial Least Square (PLS) analysis method. The PLS model is utilized to examine and determine the extent of influence among variables. The research population comprises 88 coffee-based SMEs participating in a partnership program in Bener Meriah Regency. The result of this research indicates that the significance test for the relationships within the Structural Model reveals strong statistical significance among various research parameters. Notably, the impact of digital competence (KD) on SMEs performance (KB) demonstrates the most robust relationship, with a substantial Std Beta value of 0.902. This pattern is consistent with the perspective of partnership programs (PK), where it exhibits significant effects on SMEs performance (KB) (0.429), digital competences (KD) (0.294), and entrepreneurial competences (KK) (0.451).